Treatment considerations for compulsive exercise in high-performance athletes with an eating disorder - Martenstyn, J. A.; Jeacocke, N. A.; Pittman, J.; Touyz, S.; Maguire, S. (Sports Medicine - Open, 2022)
Compulsive exercise is linked with poorer treatment outcomes in people with eating disorder (EDs). High-performance athletes represent a growing and complex subcomponent of the broader ED population, and emergent evidence indicates that different conceptualisations of compulsive exercise are needed in this population. Existing randomised controlled trials in ED populations have demonstrated small treatment effects on compulsive exercise compared with control groups; however, athletes were sparsely sampled across these studies. Thus, the extent to which current treatments for compulsive exercise in EDs are also effective in high-performance athletes is unknown. For this opinion paper, we sought representation from high-performance sports leadership, someone with lived experience of both an ED and high-performance athletics, and ED clinical experts. We discuss the utility of recommending exercise abstinence in ED treatment with athletes, as well as a number of other treatment strategies with some evidence in other contexts for further consideration and research in this population. These include using mindfulness-based interventions as an adjunct to cognitive-behavioural therapies, using wearable technologies and self-reported fatigue to inform training decisions, and incorporating greater exercise variation into training programs. We also offer practical considerations for clinicians seeking to apply foundational elements of cognitive-behavioural interventions (e.g., exposure and response prevention, cognitive restructuring, behavioural experiments) into an ED treatment program for a high-performance athlete. Future research is needed to examine characteristics of pathological compulsive exercise in athletes and whether available treatments are both feasible and effective in the treatment of compulsive exercise in athletes with an ED.